1987
DOI: 10.1002/jlac.198719870862
|View full text |Cite
|
Sign up to set email alerts
|

Optical Resolution of (±)‐2,3‐Dihydro‐2‐phenyl‐4H‐1‐benzothiopyran‐4‐one

Abstract: Optical resolution of the title compound was achieved wing the opticaUy active reagent ( 9 tS+phenetbyl)mniomazide (2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…9 Its chemical resolution was carried out with (ϩ)-(1-phenylethyloxamoyl)hydrazine 7, a carbonyl derivatizing agent 10-13 (Scheme 1). In contrast to previous findings, [10][11][12][13] where the resolution of chiral ketone derivatives with 7 resulted in the two corresponding diastereomers, which could be separated by fractional crystallization, the condensation of rac-6 with this reagent, monitored by TLC, showed the formation of four products of comparable ratio instead of two. The 1 H NMR spectrum of the crude product clearly indicated that the syn Z-and anti E-isomers of both diastereomers [(Z )-(ϩ)-8/(E )-(ϩ)-8, (Z )-(Ϫ)-8/(E )-(Ϫ) -8] were present in this mixture (Scheme 1).…”
Section: Resultscontrasting
confidence: 99%
“…9 Its chemical resolution was carried out with (ϩ)-(1-phenylethyloxamoyl)hydrazine 7, a carbonyl derivatizing agent 10-13 (Scheme 1). In contrast to previous findings, [10][11][12][13] where the resolution of chiral ketone derivatives with 7 resulted in the two corresponding diastereomers, which could be separated by fractional crystallization, the condensation of rac-6 with this reagent, monitored by TLC, showed the formation of four products of comparable ratio instead of two. The 1 H NMR spectrum of the crude product clearly indicated that the syn Z-and anti E-isomers of both diastereomers [(Z )-(ϩ)-8/(E )-(ϩ)-8, (Z )-(Ϫ)-8/(E )-(Ϫ) -8] were present in this mixture (Scheme 1).…”
Section: Resultscontrasting
confidence: 99%